Atención integral de salud a mujeres adultas con malnutrición por exceso. Centro de Salud La Vicentina, Tungurahua, 2016: A comprehensive health care to adult women with excess malnutrition. Health Center La Vicentina, Tungurahua, 2016 (La U Investiga, 2019)
Obesity is a chronic disease of multifactorial etiology. A descriptive study - transverse to characterize the comprehensive health care in adult women with overweight was treated at the Health Center Vicentina province Tungurahua, 2015. The sample consisted of 94 women aged 20 to 64 years with malnutrition and excess stratified randomly selected. The 52.12% are overweight patients and 34, 04% to the group 20 to 39 years. The 48.94% were married, 60.63% secondary school level, mestizas the 88.30%, 88.30% showed the inadequate medical care, overweight and obese 44.66% 24.46% grade I contribute most of cases with inadequate follow-up. It was concluded that the prevalence of malnutrition was in excess and overweight women in the group of 20-39 years. Comprehensive medical care in most women with excessmalnutrition, studied, proved inadequate.
Keywords: overweight; obesity; comprehensive medical care